2016
DOI: 10.1002/anie.201510403
|View full text |Cite
|
Sign up to set email alerts
|

Delocalization and Valence Tautomerism in Vanadium Tris(iminosemiquinone) Complexes

Abstract: To survey the noninnocence of bis(arylimino) acenaphthene (BIAN) ligands (L) in complexes with early metals, the homoleptic vanadium complex, [V(L)3 ] (1), and its monocation, [V(L)3 ]PF6 (2), were synthesized. These complexes were found to have a very rich electronic behavior, whereby 1 displays strong electronic delocalization and 2 can be observed in unprecedented valence tautomeric forms. The oxidation states of the metal and ligand components in these complexes were assigned by using spectroscopic, crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…The 1 H NMR spectrum of Y(Ph‐BIAN) 3 (Figure S1) changes only slightly with temperature, in analogy to the description of a related vanadium complex featuring highly similar ligands . This behavior disagrees with a pure doublet or quartet state, for which a T −1 dependence of the chemical shifts is expected.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…The 1 H NMR spectrum of Y(Ph‐BIAN) 3 (Figure S1) changes only slightly with temperature, in analogy to the description of a related vanadium complex featuring highly similar ligands . This behavior disagrees with a pure doublet or quartet state, for which a T −1 dependence of the chemical shifts is expected.…”
Section: Resultsmentioning
confidence: 51%
“…To the best of our knowledge, the reaction of this ligand with lanthanide halogenides has so far not been reported in a 3:1 stoichiometry . Notably, similar vanadium complexes with a related ligand have been described previously …”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…[11][12][13][14][15] In recent years, Clark and co-authors explored the reactivity and redox capability of BIAN ligands in early transition metal complexes, revealing very rich electronic behavior for such metal/ligand combination. 16,17 In contrast, iron compounds bearing BIAN ligand framework are relatively less investigated. A search in Cambridge Structural Database (CSD) showed that only several structurally characterized BIAN-Fe complexes have been reported, including those with tridentate BIAN ligands with an additional donor arm other than the two N donors.…”
Section: Introductionmentioning
confidence: 99%